Collaborative Governance: Efforts to Re-functionalize the Youtefa Bay Women's Forest Area Based on Local Wisdom - Vince Tebay (PT FORMOSA CENDEKIA GLOBAL, 2023)
The importance of governance collaboration as an effort to restore the function of the Youtefa Bay mangrove forest area which is not only as a disaster controller, but as a source of community life, managed from generation to generation with its local wisdom. The method used is library research. Where data comes from various literatures, by conducting text and discourse analysis. The results of this study indicate that the existence of mangrove forests on the coast of Youtefa Bay, Papua, is not only limited to disaster management, but is like a mother who gives life. Mangrove forests have become part of the community's customs. There is a division of territory to work; men earn a living at sea, and women are given mangrove forests as a local food source. Mangrove forests became a private space for women. Forest was later named